2014
DOI: 10.1111/ajsp.12055
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and employee well-being: The critical role of Zhong-Yong

Abstract: In the pursuit of well-being at work, work stress is always an inescapable challenge. However, existing research shows that the relationships between work stress and employee outcomes are inconsistent, which indicates that the concept of work stress needs further investigation. Moreover, Zhong-Yong serves as a cognitive strategy to coping with stress as well as being a pivotal life wisdom and practical rationality. Using a questionnaire survey, this study explores the relationship between work stress, employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 53 publications
0
75
1
Order By: Relevance
“…Work stress is a substantial factor to impact work-related well-being (Birdie et al, 2015;Burke, 2002;Chou et al, 2014). There are studies that consider work stress as indicator of a work-related wellbeing (Moeller and Chung-Yan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Work stress is a substantial factor to impact work-related well-being (Birdie et al, 2015;Burke, 2002;Chou et al, 2014). There are studies that consider work stress as indicator of a work-related wellbeing (Moeller and Chung-Yan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chou et al proved the related stress is destructive to employee well-being [50]. Moreover, the failure rates of equipment and operational risks will increase.…”
Section: Application and Suggestionmentioning
confidence: 99%
“…Empirical supports also revealed that the Middle Way (中庸, accepting the coexistence of yin and yang and emphasizing harmony) beliefs positively associated with life satisfaction (Huang et al, 2012) and mitigated the effects of stress on employee well-being and job satisfaction (Chou et al, 2014). …”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The yin - yang -mixed strategies are the apple of the Middle Way philosophy, which has produced fruitful and substantial influences in the indigenous psychology rooted in Confucian philosophy (e.g., Huang et al, 2012; Chou et al, 2014). Nevertheless, the Middle Way literature has little production in career theories or practices.…”
Section: Contributions and Limitationsmentioning
confidence: 99%